Análise proteômica do plasma seminal de carneiros Santa Inês adulto - Rêgo, João Paulo Arcelino do (2010)
Northeastern Brazil has a significant population of sheep and, among the native hairy breeds, Santa Inês is known for its good performance and adaptability to tropical environments. Recently, it has been shown that the protein profile of the seminal plasma of Santa Inês rams changes during sexual development, in concert with changes in semen parameters, such as sperm motility, morphology and concentration. However, the identity of seminal plasma proteins from these hairy rams is still unknown. Therefore, we pursued the identification of seminal plasma proteins from Santa Inês rams using a proteomic approach. Semen samples were collected from eight mature rams, and seminal plasma saved after centrifugation. Seminal plasma protein maps, obtained by two-dimensional electrophoresis, were stained with colloidal Coomassie. The gels were scanned and analyzed using PDQuest software. Protein spots were individually cut, in-gel digested with trypsin and identified after tandem mass spectrometry and database search. On average , we detected 302 spots per gel, from which 143 were present on every member of the match set generated by PDQuest. Thirty-nine spots were positively identified by mass spectrometry, corresponding to 26 different proteins. The major proteins present in the maps were the BSP-like RSVP14 and RSVP22 and the spermadhesins bodhesin 1 and 2. Other proteins detected in the maps included albumin, clusterin, peroxiredoxin, lactoferrin, transferrin, matrix metalloproteinase 2, beta galactosidase and heat shock proteins. The Identity of these proteins suggest their participation on several physiological events, such as sperm protection, regulation of sperm motility and capacitation, modification of sperm membrane and fertilization. The knowledge of the proteome of the ovine seminal plasma is a necessary step towards the understanding of the mechanisms underlying the regulation of sperm function by seminal plasma components in rams